Who won the war? - Naylor, Phyllis Reynolds (Delacorte Press, 2006)
As the end of summer approaches, the Malloy girls decide they will really try to get along with the Hatford boys before moving back to Ohio, but after all the practical jokes and competitions of the previous year, the boys just do not trust the girls.